Goiter and Laryngopharyngeal Reflux. (5th March 2012) - Hamdan, Abdul-Latif; Jabbour, Jad; Al Zaghal, Zaid; Azar, Sami T.
Abstract : The purpose of this study is to look at the prevalence of laryngopharyngeal reflux disease in patients with goiter in a group of 52 patients with goiter. All participants were asked to respond to the 9 questions on the Reflux Symptom Index (RSI). A diagnosis of LPRD based on symptoms was made for any RSI score above 10. The average score of every question was computed for all patients with goiter and compared to the corresponding average score of the controls. A P value of less than 0.05 was considered statistically significant. The total prevalence of LPRD in patients with goiter as indicated by an RSI score greater than 10 was 15.4% versus 9.1% in controls. The difference was not statistically significant (P value 0.525). Looking at the average score of the individual symptoms as listed in the RSI questionnaire, the average score of all the symptoms was higher in patients with goiter versus controls. There was no correlation between LPRD and any of the demographic variables except for nodules (P value 0.035). The presence of laryngopharyngeal symptoms in patients with goiter should alert the treating physician to the presence of laryngopharyngeal reflux disease.